2006
DOI: 10.1128/jb.188.7.2726-2729.2006
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactam Antibiotics Induce the SOS Response and Horizontal Transfer of Virulence Factors inStaphylococcus aureus

Abstract: Antibiotics that interfere with DNA replication and cell viability activate the SOS response. In Staphylococcus aureus, the antibiotic-induced SOS response promotes replication and high-frequency horizontal transfer of pathogenicity island-encoded virulence factors. Here we report that ␤-lactams induce a bona fide SOS response in S. aureus, characterized by the activation of the RecA and LexA proteins, the two master regulators of the SOS response. Moreover, we show that ␤-lactams are capable of triggering sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
213
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(226 citation statements)
references
References 20 publications
(28 reference statements)
9
213
3
1
Order By: Relevance
“…3a; Cirz et al, 2007). When comparing S. aureus LexA with those of other organisms, a conserved auto-proteolytic cleavage site is present at amino acid sequence Ala93-Gly94 (Maiques et al, 2006) corresponding to a LexA NTD of 10.5 kDa and a CTD of 12.8 kDa. Thus, the appearance of a 13 kDa fragment after MMC treatment suggests that only the CTD is visible in wild-type cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a; Cirz et al, 2007). When comparing S. aureus LexA with those of other organisms, a conserved auto-proteolytic cleavage site is present at amino acid sequence Ala93-Gly94 (Maiques et al, 2006) corresponding to a LexA NTD of 10.5 kDa and a CTD of 12.8 kDa. Thus, the appearance of a 13 kDa fragment after MMC treatment suggests that only the CTD is visible in wild-type cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SOS regulated genes carry out diverse functions in response to DNA damage such as nucleotide excision repair, translesion DNA replication, homologous recombination and cell division arrest. Of importance to bacterial pathogens, the SOS response also modulates the dissemination of mobile genetic elements expressing antibiotic resistance and virulence factors (Beaber et al, 2004;Maiques et al, 2006;Ú beda et al, 2005). In addition, it is well known that several groups of antibiotics are in fact inducers of the SOS response such as the fluoroquinolones (Cirz et al, 2005;Mesak et al, 2008), trimethoprim (Lewin & Amyes, 1991) and b-lactams (Maiques et al, 2006;Miller et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3D) and pathogenicity island genes. The concerted functions of these factors may account, in part, for the observation that SOS induction results in phage-mediated pathogenicity island dissemination among staphylococci (34,55). Striking features were observed within S. aureus stringent response-induced cells.…”
Section: Discussionmentioning
confidence: 98%
“…For S. aureus it could also be demonstrated that there is a link between induction of prophages and subsequent virulence modulation of the bacterium by antibiotics which are often used during the treatment of infections (Goerke et al, 2006a). A positive effect of blactam antibiotics on phage replication was recently described (Maiques et al, 2006). Subinhibitory concentrations of nafcillin (Stevens et al, 2007) and oxacillin (Dumitrescu et al, 2007) were found to enhance PVL expression, which is thought to contribute to worse outcomes of S. aureus infections after antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%